Improving mortality in older adult trauma patients: Are we doing better?. Issue 2 (February 2022) - Karam, Basil S.; Patnaik, Rohan; Murphy, Patrick; deRoon-Cassini, Terri A.; Trevino, Colleen; Hemmila, Mark R.; Haines, Krista; Puzio, Thaddeus J.; Charles, Anthony; Tignanelli, Christopher; Morris, Rachel
Abstract : BACKGROUND: Older adult trauma is associated with high morbidity and mortality. Individuals older than 65 years are expected to make up more than 21% of the total population and almost 39% of trauma admissions by 2050. Our objective was to perform a national review of older adult trauma mortality and identify associated risk factors to highlight potential areas for improvement in quality of care. MATERIALS AND METHODS: This is a retrospective cohort study of the National Trauma Data Bank including all patients age ≥65 years with at least one International Classification of Diseases, Ninth Revision, Clinical Modification trauma code admitted to a Level I or II US trauma center between 2007 and 2015. Variables examined included demographics, comorbidities, emergency department vitals, injury characteristics, and trauma center characteristics. Multilevel mixed-effect logistic regression was performed to identify independent risk factors of in-hospital mortality. RESULTS: There were 1, 492, 759 patients included in this study. The number of older adult trauma patients increased from 88, 056 in 2007 to 158, 929 in 2015 ( p > 0.001). Adjusted in-hospital mortality decreased in 2014 to 2015 (odds ratio [OR], 0.88; 95% confidence interval [CI], 0.86–0.91) when compared with 2007 to 2009. Admission to a university hospital was protective (OR, 0.83; 95% CI, 0.74–0.93) as compared with a community hospital admission. There was no difference in mortality risk between Level II and Level I admission (OR, 1.00; 95% CI, 0.92–1.08). The strongest trauma-related risk factor for in-patient mortality was pancreas/bowel injury (OR, 2.25; 95% CI, 2.04–2.49). CONCLUSION: Mortality in older trauma patients is decreasing over time, indicating an improvement in the quality of trauma care. The outcomes of university based hospitals can be used as national benchmarks to guide quality metrics. LEVEL OF EVIDENCE: Therapeutic/Care Management, Level IV. Abstract : Supplemental digital content is available in the text.